Edukasi Kesehatan Sebagai Intervensi Masalah Kesiapan Peningkatan Manajemen Kesehatan Lansia Dengan Riwayat Penyakit Kronis Menuju Kualitas Hidup Lansia Yang Optimal - Wulansari; Mukhamad Musta’in; Fiktina Vifri Ismiriyam (CV. Ulil Albab Corp, 2022)
Readiness to improve health management is one of the nursing problems in the behavioral category and a subcategory of counseling and learning regarding the pattern of regulation and integration of health programs into daily life that is sufficient to meet health goals. Health achievement in the elderly with chronic diseases can be improved by health education. Readiness of health management in the elderly group with chronic or degenerative diseases can occur, provided that the elderly are willing to take part in the treatment program and are curious about their own care. The purpose of providing health education has an influence on the readiness of better health management towards optimal health. The implementation method is carried out by health education including health counseling, providing alternative sources of information, as well as teaching a healthy lifestyle, and nursing therapy therapy according to problems and fulfillment of psychological health. The results of the activity show that most of the elderly have nursing problems in the prosperous category as evidenced by the level of good knowledge about their illness as much as 83% and where the elderly have understood their own care for chronic diseases. Health education is given to support the achievement of optimal health and the provision of comprehensive care. the conclusion of the activity is that all groups, both groups of nursing problems in the categories of disorders, risks and prosperity, still require health education to support health. Health workers who are around the community always provide health education